O ENSINO DE GEOGRAFIA EM UMA ESCOLA PÚBLICA DE ENSINO FUNDAMENTAL LOCALIZADA EM UM MUNICÍPIO DA AMAZÔNIA MARAJOARA - BARROS, Ariel Furtado (2024)
This article deals with "Teaching the subject of Geography in the 4th year of elementary school" with the general objective of identifying how the aforementioned teaching and learning in Geography takes place in a 4th-year class of elementary school in a public school in city of Breves. Specifically, it seeks to understand the teaching and learning dynamics of the Geography discipline and reflect on the teaching methodologies and didactic resources used in the teaching-learning process of geography. The theoretical basis seeks support from authors such as Callai (2010) and Straforini (2008). In methodological terms, the study was developed through bibliographical research and field research, with data collection through a semi- structured questionnaire. Among the results obtained, we can highlight that the teaching and learning process undertaken in the 4th year is guided by a methodology based on the oral presentation of the contents worked on from the textbook. For students, other methods are needed to make teaching meaningful. We found that about 44% of students are unable to learn the geographic knowledge taught, which may be linked to the adopted methodology. Our analysis lacks a pedagogical work that dialogues in a more dynamic and consistent way with reality and also makes clear to students the need for geographic knowledge for society. But for this, it is not enough to use different resources and try other methodologies, it is also necessary to change the objectives of teaching Geography. We conclude that the teaching of Geography in the early years must be a teaching in which students and teachers build knowledge together in a democratic and dynamic way.